Analisis Daya Tarik Wisata Pantai Lasiana terhadap Ekonomi Lokal di Kota Kupang: Studi Kasus Pelaku UMKM, Pengunjung, dan Fotografer - Ernestus Ikun; Sidelis Nenabu; Mariano L. B Mare; Gusto Winardi Kare; Agnes Susanti Indrawati; Adelheid Elisabet Loda (Jurnal Manajemen dan Ekonomi Kreatif, 2026)
Lasiana Beach is one of the coastal tourism destinations that plays an important role in stimulating local economic activities in Kupang City. This study aims to analyze the tourism attractiveness of Lasiana Beach and its impact on the local economy, particularly on micro, small, and medium enterprises (MSMEs), visitors, and photography service providers. The research employed a descriptive qualitative approach using a case study design. Primary data were collected through in-depth interviews with MSME actors, visitors, and photographers, while secondary data were obtained from relevant literature and tourism-related documents. Data were analyzed thematically by examining tourism attraction factors, visitor trends, business income changes, and local economic implications. The findings indicate that Lasiana Beach possesses several key tourism attractions, including accessibility, natural scenery, supporting facilities, and opportunities for creative economic activities. However, a decline in visitor numbers has significantly affected the income of local economic actors. The daily turnover of MSMEs decreased from approximately IDR 300,000 to IDR 50,000, while photographers’ income declined from around IDR 400,000 to IDR 24,000 per day. These findings suggest that physical tourism attractions alone are insufficient to generate sustainable economic benefits without effective promotion, proper facility management, and service innovation. Therefore, this study recommends strengthening digital marketing strategies, improving the management of MSMEs, developing tourism attractions, and enhancing collaboration among government agencies, business actors, and local communities to support sustainable tourism development and local economic growth.